Improving students' creative thinking skills through creative problem solving model based on socio-scientific issues on environmental change - Eka Putri Azrai; Rizhal Hendi Ristanto; Roza Sani Aidah (Universitas Islam Negeri Sumatera Utara, 2026)
The ability to think creatively means creating something new, honing the human brain's capacity to generate innovative ideas and conclusions that facilitate problem-solving. Efforts to enhance creative thinking skills involve several actions that must be taken, including the use of interactive learning models. This study aims to determine the improvement in students' creative thinking abilities through the socio-scientific issue-based creative problem-solving model on environmental changes. The research uses a quasi-experimental method with a Non-Equivalent pretest-posttest control group design. The research sample consisted of 61 students selected through simple random sampling. Data collection was carried out using creative thinking test instruments and observation sheets for the implementation of learning. The analysis of the research data was conducted using an independent sample t-test, which showed an improvement in students' creative thinking abilities through the socio-scientific issue-based creative problem-solving model on environmental changes. This is evidenced by the increase in the gain score, which was higher in the experimental class at 0.68, categorized as moderate. This is because students can analyze the causes and impacts of environmental changes, as well as provide science- and socially-based solutions. This learning model can be an interesting option in school education because it can trigger active participation.